An Analysis of Lexical Bundles in Research Articles: Examples from Natural and Social Sciences - Zulyanputri, Annur Karima (Universitas Pasundan, 2024)
This present research investigates the use of lexical bundles in research articles across different disciplinary areas: natural science and social science. The results showed that there are some differences in the use of lexical bundles between disciplines in the term of frequency, structures, and functions. We found that the frequency of lexical bundles can vary between natural science and social science RA. For example, the lexical bundle